2020
DOI: 10.1021/acsami.0c04303
|View full text |Cite
|
Sign up to set email alerts
|

A Nanocomposite Vehicle Based on Metal–Organic Framework Nanoparticle Incorporated Biodegradable Microspheres for Enhanced Oral Insulin Delivery

Abstract: Oral insulin delivery has revolutionized diabetes treatment, but challenges including degradation in the gastrointestinal environment and low permeation across the intestinal epithelium remain. Herein, to overcome these barriers, we developed a novel biodegradable nanocomposite microsphere embedded with metal−organic framework (MOF) nanoparticles. An iron-based MOF nanoparticle (NP) (MIL-100) was first synthesized as a carrier with an insulin loading capacity of 35%. The insulin-loaded MIL-100 nanoparticles mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 53 publications
1
71
0
2
Order By: Relevance
“…What's more, Zhou et al. 273 studied insulin loaded microspheres named Ins@MIL100/SDS@MS, which showed resistance to the stomach acid environment while absorption and transportation at intestinal after oral administration in vivo. The distribution of insulin in major organs suggested that the microsphere potentially circulated through the portal veins to the liver then into the heart, finally metabolized via the kidneys ( Fig.…”
Section: Biopharmaceutics Of Mofs and Mofs-based Ddssmentioning
confidence: 99%
See 1 more Smart Citation
“…What's more, Zhou et al. 273 studied insulin loaded microspheres named Ins@MIL100/SDS@MS, which showed resistance to the stomach acid environment while absorption and transportation at intestinal after oral administration in vivo. The distribution of insulin in major organs suggested that the microsphere potentially circulated through the portal veins to the liver then into the heart, finally metabolized via the kidneys ( Fig.…”
Section: Biopharmaceutics Of Mofs and Mofs-based Ddssmentioning
confidence: 99%
“…The distribution of insulin in major organs suggested that the microsphere potentially circulated through the portal veins to the liver then into the heart, finally metabolized via the kidneys ( Fig. 14 D) 273 . From pharmacokinetic parameter analysis, the peak level of BALB/c nude mice plasma insulin was emerged at 4 h and remained over 8 h. Moreover, contrast to the subcutaneous insulin injection, the relatively lagged absorption of oral system was likely due to the absorption process of GI tract.…”
Section: Biopharmaceutics Of Mofs and Mofs-based Ddssmentioning
confidence: 99%
“…MOFs可运载药物分子或造 影 剂 通 过 口 服 、 静 脉 注 射 和 吸 入 等 方 式 进 入 人 体 [5,36,37] . 例如, Zhou等 [39] 破坏 [48] . Li等 [49] 酸盐置换, 24 h内MIL-100降解率约为29.9%±2.1% [50] .…”
Section: Mofs在人体内的降解unclassified
“…[97] . 除此之外, Leus等 [92] 、MIL-100 [39] 、Fe-BTC和Zn-BTC [77] [47,49,54,113] . MOFs中金属种类 会影响阴离子对MOFs的降解.…”
Section: Mof-74在潮湿条件下由于金属的水解反应导致其骨unclassified
“…successfully synthesized a protective CMC/Cu‐MOF@IBU nanocomposite, which avoided the explosive release of IBU under acidic condition. Chen et al [36] . reported a MOF nanocrystalline modified with sodium dodecyl sulfate, designated as MIL100/SDS.…”
Section: Introductionmentioning
confidence: 99%